Roles of inter-SWCNT junctions in resistive humidity response - Zhang, Kang (2016)
As a promising chemiresistor for gas sensing, the single-walled carbon nanotube (SWCNT) network has not yet been fully utilized for humidity detection. In this work, it is found that as humidity increases from 10% to 85%, the resistance of as-grown SWCNT networks first decreases and then increases. This non-monotonic resistive response to humidity limits their sensing capabilities. The competition between SWCNT resistance and inter-tube junction resistance changes is then found to be responsible for the non-monotonic resistive humidity responses. Moreover, creating sp3 scattering centers on the SWCNT sidewall by monovalent functionalization of four-bromobenzene diazonium tetrafluoroborate is shown to be capable of eliminating the influence from the inter-tube junctions, resulting in a continuous resistance drop as humidity increases from 10% to 85%. Our results revealed the competing resistive humidity sensing process in as-grown SWCNT networks, which could also be helpful in designing and optimizing as-grown SWCNT networks for humidity sensors and other gas sensors.